Tomatidine relieves neuronal damage in spinal cord injury by inhibiting the inflammatory responses and apoptosis through blocking the NF-κB/CXCL10 pathway activation - Wang, Xu; Huang, Wei; Sun, Hao; Wang, Hua; Wang, Dongxu; Wang, Yongxiang (Frontiers in Pharmacology, 2024)
Background: Spinal cord injury (SCI) is a neurological disease featured with high disability and mortality rates. Tomatidine, a natural steroid alkaloid, has been evidenced to have neuroprotective properties. However, the underlying mechanisms of tomatidine in treating SCI remain ambiguous. This study aimed to illustrate the molecular mechanism of tomatidine on inflammatory response and functional rehabilitation after SCI. Methods: Sprague-Dawley (SD) rats were applied to construct an in vivo SCI model and were intraperitoneally injected with tomatidine (5, 10, or 20 mg/kg) for 7 days, followed by treated with nuclear factor-κB (NF-κB) pathway agonist (PMA). In addition, lipopolysaccharide (LPS)-induced PC-12 cells was used to establish SCI cell model and stimulated with tomatidine, PMA or CXCL10 inhibitor. The pathophysiological changes and neurological function were evaluated using BBB scoring, water content determination, HE staining and TUNEL assay. Levels of inflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, were measured. Cells proliferation, apoptosis, and the expression of C-X-C motif chemokine ligand 10 (CXCL10) were determined. Moreover, the expression of cleaved-Caspase3, Caspase3, CXCL10, p-p65 and p65 were analyzed. Results: Our data revealed that tomatidine promoted neuronal damage recovery, reduced histopathological changes, elevated cells proliferation, and inhibited the apoptosis and inflammatory factors levels in spinal cord tissues and LPS-induced PC-12 cells. Moreover, tomatidine decreased the expression of CXCL10 in vitro and in vivo, which was accompanied by regulation of the NF-κB pathway. However, the NF-κB pathway agonist PMA reversed the protective effect of tomatidine in vitro. PMA also enhanced the CXCL10 expression and stimulated the activation of the NF-κB pathway, as demonstrated by the up-regulation of phosphorylated p65. The CXCL10 inhibitor had the same effect as tomatidine on cleaved-Caspase3 expression, CXCL10 expression and NF-κB pathway. Conclusion: Tomatidine can alleviate neuronal damage in SCI via inhibiting apoptosis and inflammation through NF-κB/CXCL10 pathway. Our findings provide a novel therapeutic target and candidate for the treatment of SCI.